2022
DOI: 10.1101/2022.03.21.22272722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Another doubling of excess mortality in the United States relative to its European peers between 2017 and 2021

Abstract: Importance Previous studies have shown the pre-pandemic emergence of a gap in mortality between the United States and other high-income nations. This gap was estimated to account for nearly one in seven US deaths in 2017. Objective The number and proportion of US deaths that can be attributed to this gap is expected to have grown during the pandemic. This study aims at quantifying this growth at the end of 2021. Design This cross-sectional study uses publicly available 2017 to 2021 data on deaths from all cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Another recent study found that if the USA had the same age-specific mortality rates as other wealthy nations in 2019, there would have been 626,353 fewer deaths, with over half of these deaths occurring in people under 65 years of age 24 . These differences have grown during the pandemic 24 , 26 , with one recent analysis finding that approximately 1.1 million deaths in the USA, including half of deaths in people under 65 years, could have been averted in 2021 had age-specific mortality rates matched those of other wealthy countries 24 . The drivers of these long-standing differences in baseline mortality rates between the USA and other wealthy countries are complex, but include factors such as increasing drug overdose and suicide mortality as well as a plateau in heart disease mortality among other causes of death, with widening educational inequalities in mortality seen in the USA over the past several decades relative to other peer nations 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study found that if the USA had the same age-specific mortality rates as other wealthy nations in 2019, there would have been 626,353 fewer deaths, with over half of these deaths occurring in people under 65 years of age 24 . These differences have grown during the pandemic 24 , 26 , with one recent analysis finding that approximately 1.1 million deaths in the USA, including half of deaths in people under 65 years, could have been averted in 2021 had age-specific mortality rates matched those of other wealthy countries 24 . The drivers of these long-standing differences in baseline mortality rates between the USA and other wealthy countries are complex, but include factors such as increasing drug overdose and suicide mortality as well as a plateau in heart disease mortality among other causes of death, with widening educational inequalities in mortality seen in the USA over the past several decades relative to other peer nations 25 .…”
Section: Discussionmentioning
confidence: 99%
“…“Missing Americans” offers an alternative, easily interpretable metric: the number of U.S. deaths that would have been averted if the U.S. had the age-specific mortality rates of its peers. Our analysis builds on our (14) and others’ (11, 12) previous analyses documenting excess U.S. deaths prior to COVID-19 and during the pandemic (19), as well as work on racial disparities in excess deaths before (14, 29) and during the COVID-19 pandemic (22, 23, 30).…”
Section: Discussionmentioning
confidence: 99%
“…Our comparator set makes comprehensive use of available data on peer countries, following recent work on life expectancy trends (4,26). However, we also present "Missing Americans" estimates using two alternate comparators: the other Group of Seven (G7) countries -Canada, France, Germany, Italy, Japan, and the United Kingdom -used in prior work by members of this study team, (14) and the five largest Western European countries -France, Germany, Italy, Spain, UK -used by Preston and Vierboom (11) and Heuveline (19). Data on deaths and population denominators were obtained from the HMD, which compiles official data from national vital registries and censuses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, fixed effects models show state-level SIP policies did not impact excess mortality in the U.S. (Pugh et al, 2022). Additional studies in the U.S. have examined the impact of SIP policies on the number of COVID-19 outcomes including cases, hopsitalizations and deaths (Berry et al, 2021;Courtemanche et al, 2020;Dave, McNichols, & Sabia, 2021, 2022Lyu & Wehby, 2020). Similarly, other studies explored the relationship between the number of COVID-19 cases and deaths and the enactment of SIP policies (Jalloh et al, 2022).…”
mentioning
confidence: 99%